AKTIVITAS BIOLARVASIDA EKSTRAK ETANOL SEREH WANGI (Cymbopogon nardus L) TERHADAP MORTALITAS LARVA AEDES AEGYPTI - Putri Rahmawati, Riana; Hasriyani, Hasriyani; Nisrina Absor, Farah (Nusantara Hasana Journal, 2025)
Aedes aegypti mosquitoes  are the main vector of the spread of dengue hemorrhagic fever (DHF). These mosquito controls are often carried out with synthetic insecticides, but their use can lead to resistance and negative impacts on the environment. Therefore, a more environmentally friendly control alternative is needed, one of which is with natural biolarvicides. One example of a plant that has the potential to be a biolarvicide is citronella (Cymbopogon nardus L). This study aims to determine the biolarvicide activity of citronella ethanol extract (Cymbopogon nardus L) on the mortality of Aedes aegypti larvae  and determine the Lethal Concentration 50 (LC50) value. This research was carried out using experimental methods and data analysis techniques used, namely quantitative by calculating the LC valueof 50 using the probit analysis test on SPSS.  The results of the average percentage of mortality of Aedes aegypti larvae in group 1 (5%) was 61.3%, group 2 (10%) was 86.6%, and group 3 (15%) was 96.6%. The LC value of 50 from citronella ethanol extract (Cymbopogon nardus L) on the mortality of Aedes aegypti larvae was 3.531%. Citronella ethanol extract (Cymbopogon nardus L) has been shown to have natural biolarvicide effectiveness as the concentration of the extract increases.